DNA Barcoding reveals sexual dimorphism in Isotrias penedana Trematerra, 2013 (Lepidoptera: Tortricidae, Chlidanotinae) - Corley, Martin Francis Vanner; Ferreira, Sónia (Zootaxa, 2017)
Isotrias penedana Trematerra, 2013 was described from north Portugal based on males alone. Unidentified females were associated with the males using DNA barcoding, revealing sexual dimorphism in the species. Males and females differ in forewing shape, markings, and size, with females significantly smaller than males. The female is described and illustrated for the first time. We also document the species’ occurrence in northern Spain.